Pengaruh Risiko Kredit Dan Risiko Operasional Terhadap Profitabilitas Bank Umum Konvensional - Estefan, Novita (IJAcc, 2025)
The aim of this research is to determine the influence of credit and operational risk on profitability, to determine the influence of credit risk on profitability, and to determine the influence of operational risk on profitability partially or simultaneously in conventional banks listed on the Indonesian stock exchange. The population in this study was 46 conventional banks listed on the Indonesian stock exchange, while those that met the sampling criteria for this research were 40 conventional banks listed on the Indonesian stock exchange. The sampling technique used in this research is based on non-probability sampling using a purposive sampling approach which takes samples from the population based on certain criteria. The independent variables used in this research consist of Non-Performing Loans (NPL), Operating Expenses to Operating Income (BOPO) and the dependent variable is Profitability. The data analysis technique in this research uses the n test, Descriptive Statistics Test, Classical Assumption Test, Multiple Linear Regression Analysis Test, t Test, F Test, and Coefficient of Determination. Data processing in this research used SPSS (Statistical Package for the Social Sciences) software version 27 for Windows. The results of this research partially show that credit risk as measured through Non-Performing Loans (NPL) does not have a significant influence on bank profitability. Partially, operational risk as measured by the ratio of Operational Costs to Operational Income (BOPO) also does not have a significant influence on bank profitability. Simultaneously, credit risk and operational risk do not have a significant influence on bank profitability.